2010
DOI: 10.1523/jneurosci.3305-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Visual Receptive Field Properties of Neurons in the Superficial Superior Colliculus of the Mouse

Abstract: The mouse is a promising model in the study of visual system function and development because of available genetic tools. However, a quantitative analysis of visual receptive field properties had not been performed in the mouse superior colliculus (SC) despite its importance in mouse vision and its usefulness in developmental studies. We have made single-unit extracellular recordings from superficial layers of the SC in urethane-anesthetized C57BL/6 mice. We first map receptive fields with flashing spot stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
292
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(345 citation statements)
references
References 67 publications
(121 reference statements)
45
292
8
Order By: Relevance
“…On the other hand, while CGP injection did not affect the peak firing rate (predrug, 115.4 ± 19.2 Hz vs. CGP, 143.4 ± 25.9 Hz, n = 5; P = 0.124; Fig. 4C1-3 (Dräger and Hubel, 1975;Rhoades and Chalupa, 1977;Wang et al, 2010), cats Cynader, 1972, 1975), and monkeys (Schiller and Koerner, 1971;Cynader and Berman, 1972;Goldberg and Wurtz, 1972;Marrocco and Li, 1977;Moors and Vendrik, 1979), although they did not explicitly describe the pause between the ON and OFF responses. With the use of juxtacellular labeling, we revealed that the ON + Pause + OFF responses were observed in a variety of morphological types of sSC neurons.…”
Section: Gaba a And Gaba B Receptors Cooperatively Generate The Pausementioning
confidence: 95%
See 4 more Smart Citations
“…On the other hand, while CGP injection did not affect the peak firing rate (predrug, 115.4 ± 19.2 Hz vs. CGP, 143.4 ± 25.9 Hz, n = 5; P = 0.124; Fig. 4C1-3 (Dräger and Hubel, 1975;Rhoades and Chalupa, 1977;Wang et al, 2010), cats Cynader, 1972, 1975), and monkeys (Schiller and Koerner, 1971;Cynader and Berman, 1972;Goldberg and Wurtz, 1972;Marrocco and Li, 1977;Moors and Vendrik, 1979), although they did not explicitly describe the pause between the ON and OFF responses. With the use of juxtacellular labeling, we revealed that the ON + Pause + OFF responses were observed in a variety of morphological types of sSC neurons.…”
Section: Gaba a And Gaba B Receptors Cooperatively Generate The Pausementioning
confidence: 95%
“…The majority of sSC neurons reportedly exhibit both ON and OFF responses in response to a static visual stimulus (Schiller and Koerner, 1971; Cynader, 1972, 1975;Cynader and Berman, 1972;Goldberg and Wurtz, 1972;Dräger and Hubel, 1975;Marrocco and Li, 1977;Rhoades and Chalupa, 1977;Moors and Vendrik, 1979;Wang et al, 2010).…”
Section: The Majority Of Ssc Neurons Exhibit On + Pause + Off Responsesmentioning
confidence: 99%
See 3 more Smart Citations